Short‐wavelength Bouguer gravity anomaly and active fault distribution in the northeastern Japan arc. (9th October 2021) - Hirano, Mitsuhiro; Nagahama, Hiroyuki; Muto, Jun
Abstract: In the northeastern (NE) Japan arc, active faults have a characteristic effect upon the short‐wavelength Bouguer anomaly (SWBA). Here, we create a SWBA map based on the Fourier analysis of the latest gravity dataset and evaluate the relationship between the SWBA and active faults in the arc. Ultimately, we found that active faults are associated with negative regions or grooves in the SWBA and that the SWBA does not clearly depend on underlying geology in the arc. Accumulated volumetric strain caused by faulting in the crust over the past 3 Ma of geological time has generated these negative gravity anomalies, estimated at around ‒10 mGal at a maximum. Strain concentration zones can have negative zones of gravity anomaly affecting the patterns of the SWBA throughout in the arc, and the SWBA reflects the amount of crustal deformation with the curvature.